2019
DOI: 10.1371/journal.pone.0217223
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and vegetable intake and bones: A systematic review and meta-analysis

Abstract: Background Although intake of fruits and vegetables seemed to have a protective effect on bone metabolism, its effect on fractures remains uncertain. Methods A systematic review of randomized controlled trials (RCTs) and cohort studies (PROSPERO: CRD42016041462) was performed. RCTs and cohort studies that evaluated the combined intake of fruits and vegetables in men and women aged over 50 years were included. We considered fractures as a primary outcome measure. Changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 48 publications
0
39
0
3
Order By: Relevance
“…Consumption of fruits and vegetables is associated with a reduced risk of chronic diseases, such as cardiovascular disease, diabetes, cancer, and age-related functional decline [ 23 , 24 , 25 ]. Brondani et al [ 26 ] showed that dietary patterns rich in fruits and vegetables are associated with a reduced risk of bone fractures and the prevention of osteoporotic fractures. However, the mechanisms through which plant-rich diets achieve such effects are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of fruits and vegetables is associated with a reduced risk of chronic diseases, such as cardiovascular disease, diabetes, cancer, and age-related functional decline [ 23 , 24 , 25 ]. Brondani et al [ 26 ] showed that dietary patterns rich in fruits and vegetables are associated with a reduced risk of bone fractures and the prevention of osteoporotic fractures. However, the mechanisms through which plant-rich diets achieve such effects are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Plants are the main sources of phytochemicals, antioxidants, and anti-inflammatory agents [ 3 , 30 ]. There was an association between the increased intake of fruit and vegetables and the decrease of bone fracture risk [ 67 ]. It is suggested that antioxidants and anti-inflammatory compounds could be used for osteoporosis prevention and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is the dairy component of these foods that is largely responsible. Increasing evidence suggests that fruit and vegetables have a positive influence on bone health as they contain micronutrients and alkaline performing properties involved in bone mineralization [ 11 , 12 ]. While no difference was observed for fruit and vegetable serves for SES, results from this study show that the mean daily intake of fruit and vegetables for females (0.6, 3.4 servings) and males (0.4, 2.8 servings) were well below recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium is an essential nutrient required for PBM growth during adolescence and into adulthood [ 7 ]. There is accumulating evidence suggesting fruit and vegetables have protective effects on bone health through mediation of the body’s acid-base balance [ 11 ]. Fruit and vegetables contain alkaline-forming properties which act as a buffer for acidic-forming foods.…”
Section: Introductionmentioning
confidence: 99%